2019
DOI: 10.5217/ir.2018.00128
|View full text |Cite
|
Sign up to set email alerts
|

Successful transition from pediatric to adult care in inflammatory bowel disease: what is the key?

Abstract: The incidence of pediatric-onset inflammatory bowel disease (IBD) is on the rise, accounting for up to 25% of IBD cases. Pediatric IBD often has extensive bowel involvement with aggressive and rapidly progressing behavior compared to adult IBD. Because IBD has a high morbidity rate and can have a lifelong impact, successful transition from pediatric to adult care is important to maintain the continuity of care. Furthermore, successful transition facilitates appropriate development and psychosocial well-being a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 95 publications
(136 reference statements)
3
12
0
Order By: Relevance
“…In another study, age over 18 years was associated with a better knowledge of diagnosis and medication names than age under 14 years (94% and 89% compared with 45% and 58%, respectively). Similar to our study, others also reported 38%‐66% of medication non‐adherence in paediatric‐onset IBD, whereas adults show a better adherence to the treatment (69%‐82%) . A structured transition service was perceived as very important by 80% paediatric gastroenterologists, while 79% of adult gastroenterologists identified inadequacies in the preparation for transfer .…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In another study, age over 18 years was associated with a better knowledge of diagnosis and medication names than age under 14 years (94% and 89% compared with 45% and 58%, respectively). Similar to our study, others also reported 38%‐66% of medication non‐adherence in paediatric‐onset IBD, whereas adults show a better adherence to the treatment (69%‐82%) . A structured transition service was perceived as very important by 80% paediatric gastroenterologists, while 79% of adult gastroenterologists identified inadequacies in the preparation for transfer .…”
Section: Discussionsupporting
confidence: 85%
“…Similar to our study, others also reported 38%-66% of medication non-adherence in paediatric-onset IBD, 23 whereas adults show a better adherence to the treatment (69%-82%). 24,25 identified inadequacies in the preparation for transfer.…”
Section: Parameter N = 80supporting
confidence: 91%
See 2 more Smart Citations
“…The timing of and readiness for transition has been shown to be one of the most important factors determining the success of the process of transfer of care (7,21). Patients' readiness and involvement, disease stability and health care providers' communication are some of the factors that may contribute to this process (8,13).…”
Section: Discussionmentioning
confidence: 99%